Clinical Practice Guideline Reduces Evaluation and Treatment for Febrile Infants 0 to 56 Days of Age. (September 2020) - Mercurio, Laura; Hill, Rachel; Duffy, Susan; Zonfrillo, Mark R.
Invasive bacterial infection (IBI) is associated with significant morbidity and mortality among neonates. Clinical practice guidelines (CPGs) can expedite care and standardize management. We conducted a retrospective observational study of febrile infants aged 0 to 56 days to assess changes in clinical decision-making following febrile neonate CPG implementation in the pediatric emergency department of a tertiary care hospital. Data were reviewed pre- and post-CPG implementation, with 1-year separation for provider education. Fewer infants underwent laboratory testing (complete blood count, blood culture, urine culture, lumbar puncture), antibiotic administration, and hospital admission after implementation; the greatest decrease was observed among infants aged 29 to 56 days identified as not high risk for meningitis. Seven-day IBI readmission rate was 1% in both groups. Herpes simplex virus testing and treatment did not differ significantly between groups. These results suggest that CPGs can enable both standardized care and decreased intervention in this population with no change in 7-day readmission rates.